Structural, enzymatic and spatiotemporal regulation of PP2A-B55 phosphatase in the control of mitosis - Lacroix, Benjamin; Lorca, Thierry; Castro, Anna (Frontiers in Cell and Developmental Biology, 2022)
Cells require major physical changes to induce a proper repartition of the DNA. Nuclear envelope breakdown, DNA condensation and spindle formation are promoted at mitotic entry by massive protein phosphorylation and reversed at mitotic exit by the timely and ordered dephosphorylation of mitotic substrates. This phosphorylation results from the balance between the activity of kinases and phosphatases. The role of kinases in the control of mitosis has been largely studied, however, the impact of phosphatases has long been underestimated. Recent data have now established that the regulation of phosphatases is crucial to confer timely and ordered cellular events required for cell division. One major phosphatase involved in this process is the phosphatase holoenzyme PP2A-B55. This review will be focused in the latest structural, biochemical and enzymatic insights provided for PP2A-B55 phosphatase as well as its regulators and mechanisms of action.